2013
DOI: 10.1007/s12020-013-9935-9
|View full text |Cite
|
Sign up to set email alerts
|

Should patients with remnants from thyroid microcarcinoma really not be treated with iodine-131 ablation?

Abstract: a significant part of low risk DTC patients, for whom RAI is not recommended, presents an incidental suspicion of lymph-nodal involvement at WBSt confirmed by subsequent SPECT/CT. Such setting would have not been treated by I-131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
4
17
0
4
Order By: Relevance
“…These values are much lower than previous reports using the dynamic risk stratification system (11,12,13). We excluded patients with microcarcinomas in this study because of the controversy in using remnant RAI ablation for patients with microcarcinoma (24,25,26). Moreover, we only included patients who underwent surgery between 2000 and 2005 because routine neck US was performed during follow-up after 2000.…”
Section: Discussionmentioning
confidence: 99%
“…These values are much lower than previous reports using the dynamic risk stratification system (11,12,13). We excluded patients with microcarcinomas in this study because of the controversy in using remnant RAI ablation for patients with microcarcinoma (24,25,26). Moreover, we only included patients who underwent surgery between 2000 and 2005 because routine neck US was performed during follow-up after 2000.…”
Section: Discussionmentioning
confidence: 99%
“…R. Gallicchio и соавт. [67] провели ретроспектив-ное исследование 91 случая микрокарциномы низко-го риска с моно-или мультифокальным ростом без других факторов риска, которым не проводили РЙТ. Пациентам выполнены диагностическое сканирова-ние всего тела (СВТ) и однофотонная эмиссионная компьютерная томография (SPEСT-CТ).…”
Section: показания к рйтunclassified
“…Another study using diagnostic SPET-CT found that T1a tumors were associated with nodal metastases in 28/49 (57 %); unsuspected distant metastases were found in 2/49 cases (4 %) [24]. In a study of thyroid microcarcinoma, SPET-CT on post-therapy imaging was used to confirm a significant proportion (26/30 patients) as having regional nodal metastatic disease: the proportion of patients with N1 disease was 30/85 (35 %) [84].…”
Section: Comparison With Other Imaging Modalities In Thyroid Cancermentioning
confidence: 99%